A review of COVID vaccines: success against a moving target. Issue 1 (5th November 2022) - Chong, S H; Burn, L A; Cheng, T K M; Warr, I S; Kenyon, J C
Abstract: Background: Multiple vaccine platforms against COVID-19 have been developed and found safe and efficacious at a record speed. Although most are effective, they vary in their ease of production and distribution, their potential speed of modification against new variants, and their durability of protection and safety in certain target groups. Sources of data: Our discussion is based on published reports of clinical trials and analyses from national and global health agencies. Areas of agreement: The production of neutralizing antibodies against the viral spike protein is protective, and all vaccines for which published data exist have been found to be effective against severe disease caused by the viral strain they target. Areas of controversy: The degree to which vaccines protect against emerging variants, moderate disease and asymptomatic infection remains somewhat unclear. Growing points: Knowledge of the duration of protection and its decay is increasing, and discussions of booster frequency and target strains are ongoing. Areas timely for developing research: The global effort to combat transmission and disease continues to rely upon intense epidemiological surveillance, whilst real-world data and clinical trials shape vaccination schedules and formulae.